Towards a location sensitive R&D policy. Local buzz, spatial concentration and specialisation as a challenge for urban planning – Empirical findings from the life sciences and ICT clusters in Vienna. (November 2016) - Musil, Robert; Eder, Jakob
Abstract: Against the background of the increasing relevance of international co-operation and knowledge networks, the relevance of local buzz for R&D activities is being called into doubt. This has implications for urban R&D policies, as local milieus, face-to-face contacts and proximity are key factors of an urban economy. Based on the case of Vienna, it is the intention of this paper to explore the extent of spatial proximity and the role of urban R&D policy. When examining the spatial structure of 1363 R&D units, two relevant clusters (life sciences and ICT) can be identified by a quantitative GIS analysis. Furthermore, a qualitative survey gives insights into the relevance of R&D policies and their spatial implications. The findings clearly show that urban stakeholders have to consider the location sensitivity of R&D actors as well as the need for specialisation in academic niches. Highlights: Nearest neighbour hierarchical clustering allows us to identify R&D clusters in Vienna in an unprejudiced way We discuss the location sensitivity of life sciences (LS) and information and communications technology (ICT) clusters Sector specific tendencies for spatial proximity and concentration in urban R&D activities are investigated We use the findings from expert interviews to evaluate R&D policies in Vienna